1991
DOI: 10.1149/1.2085577
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the Early Stages of the Pitting Corrosion of Aluminum

Abstract: The initial stages of pitting of aluminum, under constant applied current in 1N HC1 at 65~ have been studied using millisecond current pulses and pit size distributions measured with scanning electron microscopy. Comparison of the faradaic current with the total pit area determined from SEM indicated that metal dissolution from pits is at a constant apparent current density of about 6 A/cm ~. However, the pit sizes at early times show that the equivalent current density of initial pit growth is over 100 A/cm 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 0 publications
5
41
2
Order By: Relevance
“…22 They found that the total volume of the submicrometer-size pits formed at these small etch times exceeded by a factor of ten the faradaic equivalent volume of the charge passed. Thus, the pit volume could not be explained by anodic dissolution.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…22 They found that the total volume of the submicrometer-size pits formed at these small etch times exceeded by a factor of ten the faradaic equivalent volume of the charge passed. Thus, the pit volume could not be explained by anodic dissolution.…”
Section: Resultsmentioning
confidence: 97%
“…Positron measurements were conducted in a vacuum chamber at a pressure of about 10 Ϫ7 Torr. A monoenergetic positron beam was produced by the 22 Na source in the chamber. The beam implanted positrons within the sample at a mean depth given by z m ϭ 14.8E b 1.6 ͓1͔ where the mean depth z m is in units of nanometers and the beam energy E b is in kiloelectronvolts.…”
Section: Methodsmentioning
confidence: 99%
“…Results are shown for tunnels at 70°C with initial pit half-widths from 0.15 to 0.5 m. This range corresponds to the spectrum of pit sizes found in etching experiments at this temperature. 12,24 The tunnel width and tip concentration of short tunnels with parallel walls are not affected significantly by the initial pit size. However, the pit size influences the tapering-width regime of tunnel growth: larger pits are associated with smaller rates of taper ͑larger ͒.…”
Section: Resultsmentioning
confidence: 99%
“…These pits are formed within milliseconds after the application of current. 24 The pit bottom is parallel to the outside surface. The electrolyte concentration in the pit is initially C b , and the entire pit surface is uniformly dissolving.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…After nucleation of etch pits, there is a stage of rapid dissolution in which they grow to sizes of 0.1-1 p.m in a few milliseconds; afterward, their dissolution rate (or dissolution current density) is apparently constant and approximately the same as in tunnels. 3 The dissolution rate in etch pits is uniform along their walls (Fig. 3).…”
Section: Infroductionmentioning
confidence: 95%